Influence of Fluid Replacement on Short-Term Recovery and Subsequent Exercise Performance : 液體補充對短期恢復及隨後運動時能力之影響 - WONG, Stephen H. S. (Asian Journal of Physical Education & Recreation, 1998)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Rapid fluid replacement and replenishment of muscle glycogen after prolonged exercise are vital for optimal substrate provision, cardiovascular function, and thermoregulation during subsequent bouts of vigorous exercise on the same day. This paper reviews recent work relating to the effects of rehydration with carbohydrate-electrolyte solutions during a short-term recovery period on hydration status, physiological responses, and subsequent endurance capacity. Issues investigated and discussed were drinking patterns, amount of carbohydrate (CHO) consumed, and the volume of fluid ingested. The data are presented as a series of summaries of experiments, followed by a discussion of the implications. The main findings of the studies reported suggest that in order to achieve euhydration during short-term recovery, a volume of fluid substantially larger than that lost must be ingested. The provision of additional CHO would be expected to restore the body's CHO stores to a greater extent than a smaller amount of CHO during the recovery and, thereby, improve the subsequent endurance capacity. However, this was not the case. It appears that the ingestion of large amounts of CHO, during a short recovery period, resulted in disturbances in fat and CHO metabolism which prevented an improvement in endurance capacity during subsequent exercise, after consumption of the additional CHO. 運動後迅速補充水份及恢復肌肉內的糖元對同日要進行的激烈運動十分重要，因爲能量代謝、心肺功能及體溫調節也以此爲基礎。本文主要綜述最近有關此課題之研究，旨在探討在含有碳水化合物及電解質之飮品影響下，體內水份所作出之調節、各項生理變化及恢復後之運動能力。研究結果顯示，若要在短時間之恢復期內重新達至水份平衡，人體有需要攝取比在運動時所失去之水份爲多之液體。在此短暫恢復期間，若攝取大量的碳水化合物將會引致能量代謝出現不正常的反應，並會影響隨後的運動能力。